Conservation Priorities and Environmental Offsets: Markets for Florida Wetlands - Aronoff, Daniel; Rafey, Will (American Economic Review, 2026)
We introduce an empirical framework for valuing markets in environmental offsets. Using newly-collected data on wetland conservation and offsets, we apply this framework to evaluate a set of decentralized markets in Florida, where land developers purchase offsets from long-lived producers who restore wetlands over time. We find that offsets led to substantial private gains from trade, creating $2.4 billion of net surplus from 1995–2020 relative to direct conservation. Offset trading also generated new hydrological externalities. A locally differentiated Pigouvian tax would have prevented $1.6 billion of new flood damage while preserving more than two-thirds of the private gains from trade.